Avaliação do sistema de abastecimento público de água do município de Tailândia-PA - BRAGA, Leonan de Souza (2019)
There is no doubt about the importance of water for the survival of living beings, therefore it is necessary that the water has quality and meets the required demands. As urban areas grow, it became necessary to use Water Supply Collective Cystems – WSCS to meet urban communities. Based on this, was proposed improvements in management, up to the National Information System on Sanitation-SNIS. The WSCC's are fundamental in a city, if they meet the established parameters, as well as the recommendations of the National Health Organization The city of Tailândia-PA, has the WSCS under concession responsibility of Pará Sanitation Company -. COSANPA, this company is also responsible for the management and operation of the system. The WSCS-Tailândia is structured by an underground collection, consisting of 02 deep wells and 26 shallow wells, pipeline, reservation, treatment and distribution, the treatment by simple chlorination without the application of fluoride, which is foreseen in the Ordinance 2,914 / 2011 of the Ministry of Health, the distribution occurs inefficiently, serving only 20% of the population. It is necessary to adopt measures to improve intense WSCS operation, such as the use of hydrometers and expansion of the distribution network.